2020
DOI: 10.3390/microorganisms8101470
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hepatitis B Virus Genetic Variation, Integration, and Lymphotropism in Antiviral Treatment and Oncogenesis

Abstract: Chronic Hepatitis B Virus (HBV) infection poses a significant global health burden. Although, effective treatment and vaccinations against HBV are available, challenges still exist, particularly in the development of curative therapies. The dynamic nature and unique features of HBV such as viral variants, integration of HBV DNA into host chromosomes, and extrahepatic reservoirs are considerations towards understanding the virus biology and developing improved anti-HBV treatments. In this review, we highlight t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 166 publications
(256 reference statements)
3
14
0
2
Order By: Relevance
“…In addition, BCP double mutation T1762/A1764 is more frequent in genotype C compared to genotype B increasing the risk for HCC [ 47 ]. In those patients infected with genotype B, non-cirrhotic HCC early onset is more common; whereas, genotype C is associated with cirrhotic HCC late-onset [ 48 ]. Nonetheless, chronically HBV-infected Japanese patients treated with NAs indicated that those infected with genotype B had a higher probability of HBsAg loss during treatment than those infected with genotype C [ 46 ].…”
Section: Hbv Genotypes and Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, BCP double mutation T1762/A1764 is more frequent in genotype C compared to genotype B increasing the risk for HCC [ 47 ]. In those patients infected with genotype B, non-cirrhotic HCC early onset is more common; whereas, genotype C is associated with cirrhotic HCC late-onset [ 48 ]. Nonetheless, chronically HBV-infected Japanese patients treated with NAs indicated that those infected with genotype B had a higher probability of HBsAg loss during treatment than those infected with genotype C [ 46 ].…”
Section: Hbv Genotypes and Variantsmentioning
confidence: 99%
“…Besides BCP and pre-core mutations, viral variants within the X and pre-S1 region are also associated with the risk of HCC development. Failure in NAs treatment associated with HBV mutations allows the replicative state of HBV raising the viral load and, together with the previously mentioned mutations, increases the risk of HCC development [ 48 ]. Teng et al demonstrated that the presence of deletions into the pre-S region is related to the risk or recurrence of HCC [ 50 ].…”
Section: Hbv Genotypes and Variantsmentioning
confidence: 99%
“…Despite the availability of effective drug interventions that reduce or prevent complications in most cases, chronic hepatitis B (CHB) remains a major public health issue worldwide that poses a significant health burden [ 1 ]. As the causative agent of CHB, human hepatitis B virus (HBV) is a hepatotropic DNA virus that can trigger acute and chronic hepatitis, contributing to HBV-related cirrhosis and even hepatocellular carcinoma [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The inability of existing drugs to enter the nucleus and clear the cccDNA is the main cause of CHB infection and recurrence in “functional cure” patients with negative HBsAg findings after drug withdrawal [ 10 , 11 , 12 ]. In addition, integration of the HBV and host cell genomes occurs during the process of viral replication, which is closely related to chronic infection and the occurrence of hepatoma [ 13 , 14 ]. In recent years, several studies have been performed to research and analyze the life cycle of HBV, through which many novel promising drug targets have been unveiled ( Figure 1 ) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%